Financial Constraints and the Cyclicality of R&D Investment: Evidence from Slovenia - Simona Bovha-Padilla; Joze P. Damijan; Jozef Konings (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
This paper uses firm level data to show how R&D investment responds to shocks in sales growth in credit constrained firms. A credit constrained firm has to rely on its cash flow and borrowing capacity to survive its short-run liquidity shock when hit by a negative shock. This reduces the possibility for further borrowing in order to invest in non-tangible long tfirm R&D, hence a negative shock should hit R&D investments more in firms that are more credit constrained. We find that in financially constrained firms sales growth is positively associated with R&D investment, suggesting procyclical behavior of R&D investment in credit constrained firms. In contrast, we find that in firms with no financial constraints R&D investment is negatively correlated with sales growth, suggesting countercyclical behavior of R&D, consistent with the Schumpeterian idea of restructuring. Furthfirmore, we find that the firm level response in R&D investment to sales growth is stronger in firms that are more financially dependent, such as firms that are no part of a multinational, firms not receiving subsidies or firms with less collateral.
Keywords: 330; R&D investment; financial constraints; cyclicality; Forschungskosten; Verschuldungsrestriktion; Konjunktur; Slowenien